The simplified expression of [tex]log_8 (\frac{64r^{6}}{m^{3}})[/tex] is [tex]2 +6\; log_8 \;r - 3 \;log_8\; m[/tex]
[tex]log_8 (\frac{64r^{6}}{m^{3}})=2 +6\; log_8 \;r - 3 \;log_8\; m[/tex]
A logarithm is the power to which a number must be raised in order to get some other number .
Rules:
The given expression is: [tex]log_8 (\frac{64r^{6}}{m^{3}})[/tex]
Using the property,
[tex]log(\frac{a}{b})[/tex] = log a - log b
So,
[tex]log_8 (\frac{64r^{6}}{m^{3}})= log_8 \;64r^{6} - log_8\;{m^{3}}[/tex]
Now using the property,
[tex]log a^{b} = b \;log a[/tex]
So, [tex]log_8 (\frac{64r^{6}}{m^{3}})= log_8 \;(2r)^{6} - log_8\;{m^{3}}[/tex]
[tex]log_8 (\frac{64r^{6}}{m^{3}})= 6\;log_8 (2r) - 3 \;log_8 m[/tex]
Now using the property,
log (ab)= log a + log b
we get, [tex]log_8 (\frac{64r^{6}}{m^{3}})= 6 [\;log_8 \;2 + log_8 \;r ]- 3 \;log_8 m[/tex]
[tex]log_8 (\frac{64r^{6}}{m^{3}})= 6 \;log_8 \;2 +6\; log_8 \;r - 3 \;log_8\; m[/tex]
[tex]log_8 (\frac{64r^{6}}{m^{3}})= 6 * \frac{1}{3} +6\; log_8 \;r - 3 \;log_8\; m[/tex]
[tex]log_8 (\frac{64r^{6}}{m^{3}})=2 +6\; log_8 \;r - 3 \;log_8\; m[/tex]
Hence the simplified expression is :[tex]log_8 (\frac{64r^{6}}{m^{3}})=2 +6\; log_8 \;r - 3 \;log_8\; m[/tex]
Learn more about the Logarithm here:
https://brainly.com/question/20785664
#SPJ1